The Role of Clarithromycin (Klaracid) In the Treatment Of Community Acquired Chest Infection. - Khan, Muhammad Ali; Shah, Syed Musanif; Saeedi, Muhammad Ilyas (Journal of Postgraduate Medical Institute, 2011)
Chest infection are common and can be potentially serious if not treated in time. The development of infection are normally prevented by pulmonary defence mechanism. Major pathogens associated with community acquired chest infections include streptococcus pneumonae, hemophilus influenza and mycoplasma pneumonae. Standard treatment is with penicillin derivative or erythomicin. Clarithomycin is a new macrolide antibiotic with extended activity against many of the pathogens associated with chest infection. Addition of new antibiotics is always welcomebecause of the emergency of resistant strains.